A Calibration Device to Compare Body Plethysmographs Among Pediatric Lung Function Laboratories - Demoulin, Bruno; Ioan, Iulia; Duvivier, Claude; Bonabel, Claude; Schweitzer, Cyril; Marchal, François; Demoulin-Alexikova, Silvia (Frontiers in Physiology, 2018)
Multi-center studies in specific airway resistance have shown significant inter laboratory variability. Comparison of plethysmographic equipments using a lung model easily transportable from one site to another should be of help to international normative studies. A resistor made of parallel capillary tubes - insuring adequate linearity within 1 L/sec – was connected to a glass bottle. Thermal time constants were measured while the bottle was empty and while stuffed with steel wool. In the latter, isothermal condition was estimated to occur only at very low frequency (around 0.01 Hz) and gas compression was polytropic up to 0.6 Hz. With the empty analogue, adiabatic gas compression was estimated to occur at frequencies > 0.2 Hz, and more accurate volume estimation was obtained. The empty analogue volume and specific resistance measured in a body plethysmograph on different days indicated within 5% accuracy as well as intersession repeatability. It is concluded that a physical analogue built out of simple material provides accurate measurements of specific airway resistance. The apparatus should be of help to compare plethysmographic equipments from different laboratories.